Strategic Information System Planning using Anita Cassidy Method and Design Thinking - Sambadagni, Sabella Yasmin; Fibriani (SCOPUS ID=57192643331), Charitas (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
The rapid development of information technology in recent decades has significantly impacted various sectors, including education. The D3 Informatics Engineering Study Program at the Faculty of Information Technology, Satya Wacana Christian University, needs to formulate a strategic plan to leverage technology in addressing educational challenges. This study identifies the lack of documentation for student assignments and projects as a key issue, which hampers accessibility and evaluation processes. The Anita Cassidy method and the Design Thinking approach are employed to develop an information system strategy that aligns with academic objectives and supports business processes. The Anita Cassidy method—through the stages of visioning, analysis, direction, and recommendation—facilitates the alignment of information system strategies with academic goals, resulting in recommended system features for development. Meanwhile, Design Thinking is applied to interface design development, focusing on user interaction to enhance the likelihood of system adoption and user satisfaction. This study aims to produce information system recommendations and user interface designs for the archiving of assignments in the D3 Informatics Engineering Study Program, with the goal of improving efficiency and effectiveness in managing student assignments.